8.A. Round table: Governing digital transformations in health: Shaping the digital future of Europe. (20th October 2021) - ,; ,
Abstract:  : Digital and data tools are fundamentally changing approaches to health and the design of health systems and health services deliver, but governance models have neither followed nor kept up with the pace of innovation. In response to this challenge, The Lancet & Financial Times Commission Governing health futures 2030: Growing up in a digital world is exploring the convergence of digital health (DH), AI, and other frontier technologies with UHC to support attainment of SDG 3. The COVID-19 pandemic has presented unprecedented challenges, with serious implications for public health and healthcare systems worldwide. With online work and education having become the new norm, the COVID-19 pandemic has exponentially heightened the need to develop digital skills and literacy, while simultaneously revealing and exacerbating existing disparities in digital access and skills, thus widening existing digital divides. That being said, COVID-19 has accelerated the radical implementation and widespread adoption of digital technologies, providing opportunities for improved overall health and well-being outcomes, which may extend well into the future if appropriately and sustainably implemented, evaluated, and most importantly, governed. The findings and recommendations arising from the Commission's report, which will be presented and discussed, are fully aligned with this year's conference theme, "Public health futures in a changing world." From the outset, the Commission framed its work through the notion that digital transformations, and the technologies that drive them, must be led by public value and governed to benefit population health and well-being. With growing investment in DH technologies in Europe, and increased recognition of governance challenges related to this field, this workshop offers an important and timely opportunity to present the Commission's work and discuss the implications of its findings and recommendations for European countries. The discussion in this workshop will centre around a set of critical questions, drawing from the experiences of experts involved in governance in the European context: Is the European DH ecosystem fit for purpose? To what extent is Europe's current legislative ecosystem and technical infrastructure capable of hosting digital transformations in health? Will the EHDS succeed in promoting citizens' control over their health data across Europe? How can national/regional approaches to governance of digital technologies and data better support public health outcomes and ensure that all Europeans can benefit from digital transformations in health and that no one is left behind? Workshop format: Opening remarks from each speaker to contextualise their work on DH governance in Europe and respond to the Commission's work (5 mins. each) Moderated roundtable discussion between panellists (15 mins.) Hearing & addressing audience questions/concerns (20 mins.) After the workshop, a policy brief and accompanying news article will be shared on the Commission's website. Speakers/Panelists: Ilona Kickbusch Graduate Institute of International and Development Studies, Geneva, Switzerland Andrew Wyckoff Directorate for Science, Technology and Innovation, OECD, Paris, France Andrzej Rys European Commission, DG SANTE, Brussels, Belgium Anna Odone University of Pavia, Pavia, Italy Ioana-Maria Gligor Digital Health, European Reference Networks Unit, DG Health and Food Safety, European Commission, Brussels, Belgium Key messages: The Lancet & Financial Times Governing health futures 2030 Commission report provides key recommendations for health governance and harnessing digital development for improving health outcomes. With growing investment in digital technologies in Europe, there remain governance challenges in ensuring all Europeans benefit from digital transformations in health and that no one is left behind.